Drivers for adopting Malaysian timber certification scheme/programme for the endorsement of forest certification chain of custody certification in Malaysia - Murughan, M.; Roslan, Mohamad M.K.; Zubaidah, H.; Johar, M.; Seca, G.; Pakhriazad, H.Z. (Forest Research Institute Malaysia, 2024)
The Malaysian Timber Certification Scheme/Programme for the Endorsement of Forest Certification (MTCS/PEFC) chain of custody (CoC) certification was introduced in 2001. Currently, Malaysia holds the highest number of CoC certification certificate holders in the Southeast Asia region under the PEFC global. While the number of MTCS/PEFC CoC certification certificate holders has been increasing significantly over the last two decades, it is important to explore what drives these timber and timber products companies to adopt this certification. Thus, a close-ended questionnaire, which includes three sections namely company information, external driver mechanisms (e.g. market, signalling, legal, and incentive), and internal driver mechanism (e.g. moral and learning) were sent to the 341 MTCS/PEFC CoC certification certificate holders via an official email. A total of 86 completed questionnaires were received. Results showed that signalling has emerged as the most important driver mechanism for the adoption of this certification, followed by market, legal, moral, learning, and incentive driver mechanisms. The external drivers were more valued than the internal drivers among timber and timber products companies in adopting the MTCS/PEFC CoC certification.